Ageing assessment of a wind turbine over time by interpreting wind farm SCADA data. (February 2018) - Dai, Juchuan; Yang, Wenxian; Cao, Junwei; Liu, Deshun; Long, Xing
Abstract: Ageing of a wind turbine and its components is inevitable. It will affect the reliability and power generation of the turbine over time. Therefore, performing the ageing assessment of wind turbines is of significance not only to optimize the operation and maintenance strategy of the wind turbine but also to improve the management of a wind farm. However, in contrast to the significant number of research on wind turbine condition monitoring and reliability analysis, little effort was made before to investigate the ageing led performance degradation issue of wind turbines over time. To fill such a technology gap, four SCADA-based wind turbine ageing assessment criteria are proposed in this paper for measuring the ageing resultant performance degradation of the turbine. With the aid of these four criteria, a reliable information fusion based wind turbine ageing assessment method is developed and verified in the end using the real wind farm SCADA data. It has been shown that the proposed method is effective and reliable in performing the ageing assessment of a wind turbine. Highlights: An effective wind turbine ageing assessment approach is developed based on SCADA data analysis. Four criteria for performing ageing assessment are proposed. An information fusion based ageing assessment method is developed to achieve a reliable assessment. The proposed ageing assessment approach has been verified using the SCADA data collected from operating wind turbines.